Physics of Laser Materials Processing Theory and Experiment - Gladush, Gennady G.; Smurov, Igor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book describes the basic mechanisms, theory, simulations and technological aspects of Laser processing techniques. It covers the principles of laser quenching, welding, cutting, alloying, selective sintering, ablation, etc. The main attention is paid to the quantitative description. The diversity and complexity of technological and physical processes is discussed using a unitary approach. The book aims on understanding the cause-and-effect relations in physical processes in Laser technologies. It will help researchers and engineers to improve the existing and develop new Laser machining techniques. The book addresses readers with a certain background in general physics and mathematical analysis: graduate students, researchers and engineers practicing laser applications.
General problems of propagation of laser radiation in gases and plasma and physical processes on the surface of condensed media.-Mechanisms of laser processing of metal surfaces -- Plasma phenomena in laser processing of materials -- Properties and mechanisms of deep melting of materials by a cw laser beam -- Physics of remote and gas-assisted cutting with lasers -- Interaction of pulsed laser radiation with materials -- Pulsed surface plasma -- Physics of the damage and deep melting of metals by laser pulses -- Interaction of repetitively pulsed laser radiation with materials.
Keywords: Physics; Engineering; Materials; Physics; Laser Technology, Photonics; Applied and Technical Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Metallic Materials; Engineering Thermodynamics, Heat and Mass Transfer